Author Correction: Isolated Rh atoms in dehydrogenation catalysis (Scientific Reports, (2023), 13, 1, (4458), 10.1038/s41598-023-31157-y) - Wittkämper, Haiko; Hock, Rainer; Weißer, Matthias; Dallmann, Johannes; Vogel, Carola; Raman, Narayanan; Taccardi, Nicola; Haumann, Marco; Wasserscheid, Peter; Hsieh, Tzung En; Maisel, Sven; Moritz, Michael; et al. (Scientific Reports, 2023)
Correction to: Scientific Reports, published online 17 March 2023 The original version of this Article contained an error in the spelling of the author Nicola Taccardi, which was incorrectly given as Nicola Tacardi. The original Article has been corrected.
CRIS-Team Scopus Importer:2023-06-30

Capturing spatially resolved kinetic data and coking of Ga-Pt Supported Catalytically Active Liquid Metal Solutions during propane dehydrogenation in situ - Wolf, Moritz; Raman, Narayanan; Taccardi, Nicola; Horn, Raimund; Haumann, Marco; Wasserscheid, Peter (Faraday Discussions, 2020)
Supported liquid phase catalysis has great potential to unify the advantages from both, homogeneous and heterogeneous catalysis. Recently, we reported Supported Catalytically Active Liquid Metal Solutions (SCALMS) as a new class of liquid phase catalysts. SCALMS enable high temperature application due to the high thermal stability of liquid metals when compared to supported molten salts or ionic liquids. The highly dynamic liquid metal/gas interface of SCALMS allows for catalysis over single atoms of an active metal atom within a matrix of liquid gallium. In the present study, kinetic data is acquired along the catalyst bed in a compact profile reactor during propane dehydrogenation over gallium-platinum SCALMS. The reactor design allows for analysis of the temperature and gas phase composition along the catalyst bed with a high spatial resolution using a sampling capillary inside the reactor. The concentration profiles suggest enhanced deactivation of the catalyst at the end of the bed with a deactivation front moving from the end to the beginning of the catalyst bed over time on stream. Only minor amounts of side products, formed via cracking of propane, were identified supporting previously reported high selectivity of SCALMS during alkane dehydrogenation. The acquired data is supported by in situ high-resolution thermogravimetry coupled with mass spectrometry to monitor the activity and coking behaviour of SCALMS during propane dehydrogenation. The results strongly suggest an enhanced formation of coke over Al2O3-supported SCALMS when compared to SiO2 as support material.<br

Coke Formation during Propane Dehydrogenation over Ga−Rh Supported Catalytically Active Liquid Metal Solutions - Wolf, Moritz; Raman, Narayanan; Taccardi, Nicola; Haumann, Marco; Wasserscheid, Peter (ChemCatChem, 2020)
Supported Catalytically Active Liquid Metal Solutions (SCALMS) were recently described as a new class of heterogeneous catalysts, where the catalytic transformation takes place at the highly dynamic interface of a liquid alloy. Their application in alkane dehydrogenation has been claimed to be superior to classical heterogeneous catalysts, because the single atom nature of Rh dissolved in liquid Ga hinders the formation of significant amounts of coke, e. g. by oligomerisation of carbon fragments and excessive dehydrogenation. In the present study, we investigate the coking behaviour of Ga−Rh SCALMS during dehydrogenation of propane in detail by means of high-resolution thermogravimetry. We report that the application of Ga−Rh SCALMS indeed limits the formation of coke when compared to the Ga-free Rh catalyst, in particular when relating coke formation to the catalytic performance. Furthermore, the formed coke has been shown to be highly reactive during temperature programmed oxidation in 21 % O2/He with onset temperatures of approx. 150 °C enabling a regeneration of the Ga−Rh SCALMS system under mild conditions. The activation energy of the oxidation lies in the lower range of values reported for spent cracking catalysts. Monitoring the formation of coke and performance of SCALMS in situ via thermogravimetry coupled with mass spectrometry revealed the continuous formation of coke, which becomes the only process affecting the net weight change after a certain time on stream.
CRIS-Team Scopus Importer:2020-01-31
Keywords: Coke; Dehydrogenation; Gallium; SCALMS; TPO

GaPt Supported Catalytically Active Liquid Metal Solution Catalysis for Propane Dehydrogenation-Support Influence and Coking Studies - Raman, Narayanan; Wolf, Moritz; Heller, Martina; Heene-Würl, Nina; Taccardi, Nicola; Haumann, Marco; Felfer, Peter; Wasserscheid, Peter (ACS Catalysis, 2021)
Supported catalytically active liquid metal solutions (SCALMS) of Pt in Ga (2 at.-% Pt) were studied in the temperature range of 500 to 600 °C for propane dehydrogenation. A facile synthesis procedure using ultrasonication was implemented and compared to a previously reported organo-chemical route for gallium deposition. The procedure was applied to synthesize GaPt-SCALMS catalyst on silica (SiO2), alumina (Al2O3), and silicon carbide (SiC) to investigate the effect of the support material on the catalytic performance. The SiC-based SCALMS catalyst showed the highest activity, while SiO2-based SCALMS showed the highest stability and lowest cracking tendency at higher temperatures. The selectivity toward propene for the SiO2-based catalyst remained above 93% at 600 °C. The catalysts were analyzed for coke content after use by temperature-programmed oxidation (TPO) and Raman spectroscopy. While the SiC- and SiO2-supported SCALMS systems showed hardly any coke formation, the Al2O3-supported systems suffered from pronounced coking. SEM-EDX analyses of the catalysts before and after reaction indicated that no perceivable morphological changes occur during reaction. The SCALMS catalysts under investigation are compared with supported Pt and supported GaPt solid-phase catalyst, and possible deactivation pathways are discussed.
CRIS-Team Scopus Importer:2021-11-19
Keywords: coking; dehydrogenation; gallium; platinum; SCALMS; supported liquid catalysis

Highly Effective Propane Dehydrogenation Using Ga-Rh Supported Catalytically Active Liquid Metal Solutions - Raman, Narayanan; Maisel, Sven; Grabau, Mathias; Taccardi, Nicola; Debuschewitz, Jonas; Wolf, Moritz; Wittkämper, Haiko; Bauer, Tanja; Wu, Mingjian; Haumann, Marco; Papp, Christian; Görling, Andreas; et al. (ACS Catalysis, 2019)
Our contribution demonstrates that rhodium, an element that has barely been reported as an active metal for selective dehydrogenation of alkanes becomes a very active, selective, and robust dehydrogenation catalyst when exposed to propane in the form of single atoms at the interface of a solid-supported, highly dynamic liquid Ga-Rh mixture. We demonstrate that the transition to a fully liquid supported alloy droplet at Ga/Rh ratios above 80, results in a drastic increase in catalyst activity with high propylene selectivity. The combining results from catalytic studies, X-ray photoelectron spectroscopy, IR-spectroscopy under reaction conditions, microscopy, and density-functional theory calculations, we obtained a comprehensive microscopy picture of the working principle of the Ga-Rh supported catalytically active liquid metal solution.
CRIS-Team Scopus Importer:2019-10-18
Keywords: alkane; alkene; catalysis; dehydrogenation; gallium; rhodium

Isolated Rh atoms in dehydrogenation catalysis - Wittkämper, Haiko; Hock, Rainer; Weißer, Matthias; Dallmann, Johannes; Vogel, Carola; Raman, Narayanan; Tacardi, Nicola; Haumann, Marco; Wasserscheid, Peter; Hsieh, Tzung En; Maisel, Sven; Moritz, Michael; et al. (Scientific Reports, 2023)
Isolated active sites have great potential to be highly efficient and stable in heterogeneous catalysis, while enabling low costs due to the low transition metal content. Herein, we present results on the synthesis, first catalytic trials, and characterization of the Ga9Rh2 phase and the hitherto not-studied Ga3Rh phase. We used XRD and TEM for structural characterization, and with XPS, EDX we accessed the chemical composition and electronic structure of the intermetallic compounds. In combination with catalytic tests of these phases in the challenging propane dehydrogenation and by DFT calculations, we obtain a comprehensive picture of these novel catalyst materials. Their specific crystallographic structure leads to isolated Rhodium sites, which is proposed to be the decisive factor for the catalytic properties of the systems.
CRIS-Team Scopus Importer:2023-03-31

Structural Evolution of GaOx-Shell and Intermetallic Phases in Ga-Pt Supported Catalytically Active Liquid Metal Solutions - Carl, Simon; Will, Johannes; Madubuko, Nnamdi; Götz, Alexander; Przybilla, Thomas; Wu, Mingjian; Raman, Narayanan; Wirth, Janis; Taccardi, Nicola; Apeleo Zubiri, Benjamin; Haumann, Marco; Wasserscheid, Peter; et al. (Journal of Physical Chemistry Letters, 2024)
We present a comprehensive scale-bridging characterization approach for supported catalytically active liquid metal solutions (SCALMS) which combines lab-based X-ray microscopy, nano X-ray computed tomography (nano-CT), and correlative analytical transmission electron microscopy. SCALMS catalysts consist of low-melting alloy particles and have demonstrated high catalytic activity, selectivity, and long-term stability in propane dehydrogenation (PDH). We established an identical-location nano-CT workflow which allows us to reveal site-specific changes of Ga-Pt SCALMS before and after PDH. These observations are complemented by analytical transmission electron microscopy investigations providing information on the structure, chemical composition, and phase distribution of individual SCALMS particles. Key findings of this combined microscopic approach include (i) structural evolution of the SCALMS particles’ GaOx shell, (ii) Pt segregation toward the oxide shell leading to the formation of Ga-Pt intermetallic phases, and (iii) cracking of the oxide shell accompanied by the release of liquid Ga-Pt toward the porous support.
CRIS-Team Scopus Importer:2024-05-10

Supported Catalytically Active Liquid Metal Solutions: Liquid Metal Catalysis with Ternary Alloys, Enhancing Activity in Propane Dehydrogenation - Moritz, Michael; Maisel, Sven; Raman, Narayanan; Wittkämper, Haiko; Wichmann, Christoph; Grabau, Mathias; Kahraman, Deniz; Steffen, Julien; Taccardi, Nicola; Görling, Andreas; Haumann, Marco; Wasserscheid, Peter; et al. (ACS Catalysis, 2024)
The research and optimization of catalysts are instrumental in revolutionizing chemical processes and making them viable in terms of energy and resources. Supported catalytically active liquid metal solutions (SCALMS) are highly active and stable in the harsh environment of the dehydrogenation reaction of alkanes. This is attributed to their liquid and dynamic nature and their isolated catalytically active single-atom sites. SCALMS consists of a liquid metal matrix (gallium) in which a catalytically active transition metal (platinum, rhodium, palladium, or nickel) is dissolved. Binary SCALMS systems are the subject of extensive research, aiming at a better understanding for achieving optimal performance. This work uses a combined multidisciplinary approach to examine ternary systems of the active transition metal platinum with mixtures of gallium with either tin or indium. Reaction engineering and surface chemical analysis by X-ray photoelectron spectroscopy are combined with density functional theory (DFT) and machine learning force field (ML-FF) simulations. Introducing a third metal into the mixture alters the reactivity, surface composition, and concentration gradient in the liquid metal catalyst. We demonstrate that changes in catalytic reactivity correlate with changes in the surface concentration of the active transition metal platinum and of the position of the d-band center. These findings hold great promise for future research directions as they offer potential starting points for developing SCALMS systems.
CRIS-Team Scopus Importer:2024-04-19
Keywords: AIMD; dehydrogenation; DFT; ML-FF; single-atom catalysis; XPS

Top-down vs. bottom-up synthesis of Ga–based supported catalytically active liquid metal solutions (SCALMS) for the dehydrogenation of isobutane - Raman, Narayanan; Söllner, Jakob; Madubuko, Nnamdi; Nair, Sharanya Sukumar; Taccardi, Nicola; Thommes, Matthias; Haumann, Marco; Wasserscheid, Peter (Chemical Engineering Journal, 2023)
Supported catalytically active liquid metal solutions (SCALMS) catalysts consist of a liquid metal solution of an active metal (e.g., Pd, Rh, Pt, Ni) in a low melting metal (e.g., Ga, In, Sn) deposited on a porous support material. In the current study, we extend and optimize the recently developed top-down synthesis protocol (ultrasonication of gallium metal) to prepare GaPd, GaRh and GaPt SCALMS systems. We compare the morphological differences in the obtained catalyst materials achieved between this approach and the more traditional bottom-up synthesis protocol (in situ thermal decomposition of triethylamino-gallane complex) using electron microscopy. Moreover, the spatial distribution of the catalytically active material in the porous alumina support is evaluated using high resolution argon physisorption measurements. Both techniques strongly indicate that the bottom-up approach leads to a high degree of pore penetration while the gallium droplets are largely on the outer surface in case of the top-down method. Changes to the surface chemistry of the support were also investigated by means of NH3/CO2 temperature programmed desorption. All catalytic systems synthesized by the two synthesis methods, i.e., GaPd, GaRh and GaPt, were tested in a quartz, fixed-bed tubular reactor for isobutane dehydrogenation. All SCALMS materials, irrespective of their individual synthesis protocol, were significantly more active than their pure metal counterparts. The SCALMS catalyst prepared using the bottom-up approach showed initial productivity of 407 gbutenes molM–1 min−1, 832 gbutenes molM–1 min−1, and 963 gbutenes molM–1 min−1 for the GaPd, GaRh and GaPt respectively. These values represent more than twice the initial activity obtained with the top-down synthesized counterparts. This activity difference can be explained by the analytically determined difference in liquid metal droplet size distribution.
CRIS-Team Scopus Importer:2023-10-06
Keywords: Coking; Dehydrogenation; Gallium; Liquid metal; SCALMS; Supported catalyst

Unraveling Structural Details in Ga-Pd SCALMS Systems Using Correlative Nano-CT, 360° Electron Tomography and Analytical TEM - Wirth, Janis; Englisch, Silvan; Drobek, Dominik; Apeleo Zubiri, Benjamin; Wu, Mingjian; Taccardi, Nicola; Raman, Narayanan; Wasserscheid, Peter; Spiecker, Erdmann (Catalysts, 2021)
We present a comprehensive structural and analytical characterization of the highly promising supported catalytically active liquid metal solutions (SCALMS) system. This novel catalyst shows excellent performance for alkane dehydrogenation, especially in terms of resistance to coking. SCALMS consists of a porous support containing catalytically active low-melting alloy particles (e.g., Ga-Pd) featuring a complex structure, which are liquid at reaction temperature. High-resolution 3D characterization at various length scales is required to reveal the complex pore morphology and catalytically active sites’ location. Nano X-ray computed tomography (nano-CT) in combination with electron tomography (ET) enables nondestructive and scale-bridging 3D materials research. We developed and applied a correlative approach using nano-CT, 360°-ET and analytical transmission electron microscopy (TEM) to decipher the morphology, distribution and chemical composition of the Ga-Pd droplets of the SCALMS system over several length scales. Utilizing ET-based segmentations of nano-CT reconstructions, we are able to reliably reveal the homogenous porous support network with embedded Ga-Pd droplets featuring a nonhomogenous elemental distribution of Ga and Pd. In contrast, large Ga-Pd droplets with a high Ga/Pd ratio are located on the surface of SCALMS primary particles, whereas the droplet size and the Ga/Pd ratio decreases while advancing into the porous volume. Our studies reveal new findings about the complex structure of SCALMS which are required to understand its superior catalytic performance. Furthermore, advancements in lab-based nano-CT imaging are presented by extending the field of view (FOV) of a single experiment via a multiple region-of-interest (ROI) stitching approach. <
Keywords: supported catalytically active liquid metal solutions (SCALMS); catalysis; nano-CT; electron tomography; X-ray microscopy; electron microscopy